The Escherichia coli K-12 gntP gene allows E. coli F-18 to occupy a distinct nutritional niche in the streptomycin-treated mouse large intestine. - Sweeney, N J (1996)
Escherichia coli F-18 is a human fecal isolate that makes type 1 fimbriae, encoded by the fim gene cluster, and is an excellent colonizer of the streptomycin-treated mouse intestine. E. coli F-18 fimA::tet, lacking type 1 fimbriae, was constructed by bacteriophage P1 transduction of the fim region of the E. coli K-12 strain ORN151, containing the tetracycline resistance gene from Tn10 inserted in the fimA gene, into E. coli F-18. E. coli F-18 fimA::tet was found to occupy a distinct niche in the streptomycin-treated mouse intestine when fed in small numbers (10(4) CFU) to mice, along with large numbers (10(10) CFU) of E. coli F-18, as defined by the ability of the E. coli F-18 fimA::tet strain to grow and colonize only 1 order of magnitude below E. coli F-18. The same effect was observed when mice already colonized with E. coli F-18 were fed small numbers of E. coli F-18 fimA::tet. Experiments which show that the E. coli K-12 gene responsible for this effect is not fim::tet but gntP, which maps immediately downstream of the fim gene cluster, are presented. gntP encodes a high-affinity gluconate permease, suggesting that the distinct niche in the mouse large intestine is defined by the presence of gluconate. The data presented here support the idea that small numbers of an ingested microorganism can colonize the intestine as long as it can utilize an available nutrient better than any of the other resident species can.